THE STATE OF STRESSES OF THE LITHOSPHERE IN JAPAN BEFORE THE CATASTROPHIC TOHOKU EARTHQUAKE OF 11 MARCH 2011 - Yu. L. Rebetsky; A. Yu. Polets (Геодинамика и тектонофизика)
The article presents results of tectonophysical methods applied to reconstruct tectonic stress field of the north-western flank of the Pacific Ocean seismic focal zone in the region wherein the 2011 Tohoku earthquake was prepared. The reconstructions are based on earthquake foci data for the time period before the catastrophic seismic event. The field of stresses, wherein the Tohoku earthquake focus was formed, had a high gradient along the dip of the seismic focal zone. It is revealed that the focus developed in the junction area of the crust segments with high and low levels of effective pressure. A wide area of lower effective pressure was located at depths close to 30 km, and it was the most susceptible to brittle fracture. In our opinion, the area impacted by the Tohoku earthquake is large due to a large length of the crustal segments with the high gradient of stresses, which are located along the eastern part of the crust of the Honshu Island.The stress reconstruction also shows that the axis of the Japan oceanic trough divides the seismic focal zone into areas of horizontal compression (westward) and horizontal extension (eastwards). According to our calculations, lateral compression is the highest at the crustal depths up to 20 km westward of the trough’s axis, where maximum lateral compression axes are oriented orthogonally to the trough’s strike. Eastward of the trough’s axis, minimum horizontal compression axes are oriented orthogonally to the trough’s strike. At the crossing point of the Japan trough, a sharp changing of stress is by a factor of 5 to 8 of internal cohesion of rocks, τf. This sharp changing of stress is lower for the Izu-Bonin trough and varies from 3 to 5 τf.